Antibacterial coating on in-line suction respiratory catheter to inhibit the bacterial biofilm formation using renewable cardanyl methacrylate copolymer. Issue 4 (4th March 2017) - Mahata, Denial; Nag, Ahindra; Mandal, Santi M.; Nando, Golok B.
Abstract: Health-care materials associated with infections are very common in hospital admitted patients. There are generally infected by contact with the catheter or other multipurpose devices which are contacted with microbes. The respiratory infections associated with the pathogens having strong biofilm forming ability on catheter surface, causes life-threatening in every year. Therefore, a catheter coating material is of great interest which inhibits the biofilm formation of pathogens on a catheter to prevent respiratory infections. In this study, we synthesized cardanol containing copolymers as antimicrobial healthcare material via radical polymerization of cardanyl methacrylate (CMA) with styrene (St) monomer in presence of free radical initiator. The rate of polymerization was drastically reduced with the increase of feeding CMA monomer in copolymer. The thermal and mechanical properties were found to increase with incorporation of cardanol moiety in brittle and hard polystyrene. This soft copolymer was grafted onto polyvinyl chloride respiratory catheter which showed high antibacterial activity, inhibit the biofilm formation and also prevent bacterial adhesion. Therefore, the developed coating material on respiratory catheter surface is effective way to control the respiratory catheter-associated nosocomial infections.